PENGARUH KEMAJUAN TEKNOLOGI INFORMASI DAN PENGETAHUAN INVESTASI TERHADAP MINAT INVESTASI GENERASI Z DI PASAR MODAL - Sastradewi, Ni Kadek Selvia; Putra, I Nyoman Nugraha Ardana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025DO - 10.24843/EEB.2025.v14.i05.p10, 2025)
This study aims to examine the impact of Information Technology Advancement and Investment Knowledge on Generation Z's Investment Interest, focusing on students of the Faculty of Economics and Business at the University of Mataram. The research data were obtained through questionnaires distributed to 100 respondents selected using purposive sampling. This technique was employed to ensure that respondents met specific criteria, namely students who already possessed a basic understanding of investment. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that both Investment Knowledge and Information Technology Advancement have a positive and significant influence on Investment Interest. This study highlights the importance of financial literacy and digital technology as strategies to increase youth participation in the capital market. These findings can serve as a foundation for educational institutions and capital market regulators in designing effective policies and educational programs to sustainably attract investment interest among the younger generation. The increase in investment value in the capital market among young people is influenced by technological developments and the growing level of financial literacy.